Analysis of Factors Affecting Reporting Effectiveness in the Reporting Information System at Community Health Centers in Serang Regency - Intan Ida Nahampun; Dhany Isnaeni Dharmawan (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
The effectiveness of reporting within the reporting information system at Community Health Centers (Puskesmas) is crucial for supporting data‑driven decision‑making, health‑program planning, and performance monitoring. Accurate and timely reporting enables healthcare administrators to analyze trends, allocate resources efficiently, and improve patient outcomes through evidence‑based interventions. This article analyzes the factors influencing reporting effectiveness at Puskesmas in Serang Regency, including technological, human‑resource, and organizational factors. The study employs a literature‑review and case‑analysis approach, highlighting challenges and offering recommendations to improve reporting effectiveness. The results indicate that limitations in infrastructure, staff competency, digital literacy, as well as management support and policy, are key factors that must be addressed to optimize the reporting system in Serang Regency’s Puskesmas. Technological barriers—such as inadequate hardware, software, and internet connectivity—often hinder the seamless collection and transmission of health data. Human‑resource challenges, including insufficient training and low digital literacy among staff, can lead to data‑entry errors and delays. Organizational factors—such as clear policies, standard operating procedures, and a supportive management culture—are also essential for sustaining high‑quality reporting practices. Furthermore, the integration of health informatics and continuous quality‑improvement initiatives can enhance the reliability and usability of reported data, ultimately supporting better health outcomes at the community level. The study concludes that a holistic approach—encompassing technological upgrades, ongoing staff development, and strong organizational leadership—is necessary to ensure the effectiveness and sustainability of reporting systems in primary‑healthcare settings.